Mutant p53 as a therapeutic target for the treatment of triple-negative breast cancer: Preclinical investigation with the anti-p53 drug, PK11007. (1st February 2018) - Synnott, Naoise C.; Bauer, Matthias R.; Madden, Stephen; Murray, Alyson; Klinger, Rut; O'Donovan, Norma; O'Connor, Darran; Gallagher, William M.; Crown, John; Fersht, Alan R.; Duffy, Michael J.
Abstract: The identification of a targeted therapy for patients with triple-negative breast cancer (TNBC) is one of the most urgent needs in breast cancer therapeutics. The p53 gene is mutated in approximately 80% of patients with TNBC, and is a potential therapeutic target for patients with this form of breast cancer. The 2-sulfonylpyrimidine compound, PK11007, preferentially decreases viability in p53-compromised cancer cell lines. We investigated PK11007 as a potential new treatment for TNBC. IC50 values for inhibition of proliferation in a panel of 17 breast cell lines by PK11007 ranged from 2.3 to 42.2 μM. There were significantly lower IC50 values for TNBC than for non-TNBC cell lines (p = 0.03) and for p53-mutated cell lines compared with p53 WT cells (p = 0.003). Response to PK11007 however, was independent of the estrogen receptor (ER) or HER2 status of the cell lines. In addition to inhibiting cell proliferation, PK11007 induced apoptosis in p53 mutant cell lines. Using RNAseq and gene ontology analysis, we found that PK11007 altered the expression of genes enriched in pathways involved in regulated cell death, regulation of apoptosis, signal transduction, protein refolding and locomotion. The observations that PK11007 inhibited cell proliferation, induced apoptosis and altered genes involved in cell death are all consistent with the ability of PK11007 to reactivate mutant p53. Based on our data, we conclude that targeting mutant p53 with PK11007 is a potential approach for treating p53-mutated breast cancer, including the subgroup with TN disease. Highlights: The identification of a targeted therapy for patients with triple-negative breast cancer (TNBC) is one of the most urgent needs in breast cancer therapeutics. As p53 is mutated in approximately 80% of TNBC, it is a potential therapeutic target for this subset of breast cancer patients. The 2-sulfonypyrimidine compound, PK11007 was previously shown to preferentially decrease viability in p53-compromised cancer cell lines. Here, we show that PK11007 preferentially decreased cell viability and induced apoptosis in mutant p53 compared to wild-type p53 cell lines. PK11007 is a potential new treatment for TNBC.